Bioinspired materials for batteries: Structural design, challenges and future perspective - Wasif ur Rehman; Yanan Ma; Zahoor khan; Fatima Zahra Ait Laaskri; Jiawei Xu; Youlong Xu; Hamid Rehman; Umar Farooq; Ali Altalbe; Jian Li (Results in Chemistry)
Bioinspired materials (BIMs) have significantly impacted our daily lives by serving as essential energy sources. The main challenge for bio-inspired materials is to balance high energy storage, long-lasting performance, being environmentally friendly, and low cost, making them easy to produce at large scales. There has been considerable interest in mimicking electrode materials at the nanoscale, whether in structure or function, due to their unique benefits and enhanced performance in rechargeable batteries. In this review, we explore bioinspired structures that offer abundant active sites for ion storage and transport channels that facilitate rapid ion diffusion, thereby significantly improving electrochemical storage. This study also explored modifications to the surface and interface of smart functionalities, such as self-healing and light-responsiveness, which are essential for integrated energy storage systems. We also emphasized the promise of these BIMs in addressing existing challenges in energy storage technologies, providing valuable insights for future research and practical applications.